UJI EFEKTIVITAS EKSTRAK BAWANG DAYAK (Eleutherine palmifolia Merr) TERHADAP PENYEMBUHAN INFEKSI JAMUR Saprolegnia sp, PADA IKAN NILA - Junius Akbar (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
The purpose of this research was to know the effect Bawang Dayak(Eleutherine palmifolia Merr) in Saprolegnia sp infection of nile tilapia (Oreochromissp) with smear method. This research used Completely Randomized Desin consistedone factors with three treatments and three replicates (A: 10 ppt/ind), (B: 20 ppt/ind),and (C: control). The research using aquarium and nile tilapia (5-8 cm body length)with density of 2 ind/aquarium. Parameters observe were inhibitory test, recoverytime, survival rate, and water quality. The result showed that optimal consentrationBawang Dayak (Eleutherine palmifolia Merr) is 20 ppt.